Dissemination of soy milk processing machine technology and marketplaces to increase MSME productivity during the pandemic - Ellya Nurfarida; Nila Nurlina; Abidatul Izzah (Universitas Muhammadiyah Magelang, 2022)
MSME Dele Jaya is a soy milk producer in Kediri. Because MSME Dele Jaya only has a soybean grinding equipment, the soy milk boiling process has be done separately. Offline sales are still done by entrusting the product to shops, vegetable vendors, sales and resellers. The adoption of appropriate technology, such as semi-automatic 2in1 machines and web markets, is thought to aid ease work and save time. Preparation, design, fabrication of essential technologies, and mentoring in theory and practice are all part of this community service. Currently, MSME Dele Jaya has a soy milk processing equipment, a web market place www.delejaya.com, and greater skills in managing the transferred technology.